Analysing The Entrepreneurial Competencies That Characterises The Success Of Female-Led Enterprises In Ghana - Nyarko, Cynthia Oduro; Hervie, Dolores Mensah (Archives of Business Research, 2019)
Micro, Small and Medium Enterprises (MSMEs) plays an important role in the economic development of a country. There are increasing numbers of women entrepreneurs involve in this sector in recent times. Entrepreneurial competencies have been validated in Entrepreneurship studies. Hence this paper examines the entrepreneurial competencies that influence the success of their businesses since the success or failure of the venture will be affected by the skills and abilities (competencies) of owner-managers. A sample of 200 respondents were selected for a survey in Accra Metropolitan area of the Greater Accra region of Ghana. Structured questionnaire was used to collect data and using survey method. The data analysis was done using descriptive statistics. The findings of the study revealed that there is a significant positive relationship between entrepreneurial competencies and venture success.